Gas phase synthesis of two ensembles of silicon nanoparticles. (21st August 2015) - Mohan, A; de Jong, M M; Poulios, I; Schropp, R E I; Rath, J K
Abstract: Dusty plasmas provide a very favorable environment for the growth of silicon nanocrystals. For application of silicon nanocrystals in a solar cell, the fabrication of monodisperse silicon quantum dots has been challenging. We report a single step method to synthesize silicon (Si) nanoparticles in a custom designed dedicated plasma reactor. The nanoparticles produced in the gas phase belong to two different phases exhibiting different structural and optical properties. Particles made in the bulk of the plasma are aggregates of crystalline particles with a mean size of 100 nm. Particles made in locally enhanced plasma regions produced at holes present in the grounded electrode contain free-standing quantum sized particles with crystallites (with mean size of 2.95 nm) embedded within an amorphous matrix. We provide insight on different plasma processes leading to the formation of aggregates and free-standing particles. We hypothesize that the free standing particles are formed due to the excess energetic electrons present in locally enhanced discharges.